The starch addition to a curtain coating formulation and its effect on pitting - Schoenfelder, Samantha L.; Pekarovicova, Alexandra; Fleming, Paul D. (Journal of Print and Media Technology Research, 2023)
An undisclosed recycled fiber board mill installed a “two-slotted” curtain coater to replace an air knife coater, which enabled a high-quality coating without past speed limitations. With the curtain coater’s installation, however, a prominent defect arose, known as “pitting”. Pitting occurs when the coating of the sheet has small holes that mar its surface, which, when clustered together or larger in size, can cause print break-up. Starch was added to the formulation to modify rheological properties of top and bottom curtain coatings, and advance water retention capabilities of them. Results show the original formulations with no starch were more thixotropic than the starch formulations. Starch aided in reducing the low shear viscosity by as much as 25 %, which had a large impact on converting the system from a strongly elastic rheology to a more viscous one. Such a move toward a more purely viscous system helped to prevent the elastic stretching and reduced bubble formation in the coatings. Starch addition also increased water retention capabilities of the coatings. The pitting significantly decreased during these trials, with lower overall pit counts and area pitted.